Upaya Pencegahan Stunting melalui Intervensi Fisik dan Sensorik pada Ibu Hamil - Dwi Retno Agustiningsih; Tri Kristianti; Elisa Ismayanti (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2025)
Stunting is a chronic nutritional problem that affects children's physical growth, brain development, and overall quality of life. Prevention efforts should begin during pregnancy through adequate nutritional intake, maternal health care, and positive stimulation for the fetus. This community service program aimed to educate pregnant women on early stunting prevention through a combination of prenatal exercise and classical Mozart music stimulation. The method applied was Community-Based Participatory Research (CBPR) with lectures, discussions, direct practice, and Q&A sessions. The activity was conducted in Ngadirenggo Village, Wlingi District, Blitar Regency, involving 24 pregnant women in their second and third trimesters. The educational materials covered the relationship between maternal health and stunting risk, the benefits of classical music for fetal brain development, and prenatal exercise movements that promote blood circulation and nutrient distribution. The results showed high enthusiasm and active participation among attendees, with most reporting relaxation, improved physical comfort, and positive fetal responses when music was played. Prenatal exercise was also perceived as reducing muscle tension and increasing comfort during pregnancy. This program concludes that combining physical and sensory interventions can serve as a supportive strategy in stunting prevention; however, it must be complemented by optimal nutrition and regular prenatal check-ups.